2005
DOI: 10.1007/s00035-005-0709-8
|View full text |Cite
|
Sign up to set email alerts
|

Vorkommen der Kleinen Teichrose Nuphar pumila und des Hybrids N. x intermedia in der Schweiz

Abstract: Kozlowski G. and Eggenberg S. 2005. Distribution of the least water-lily (Nuphar pumila) and the hybrid N. x intermedia in Switzerland. Bot. Helv. 115: 125-136.The least water-lily (N. pumila (TIMM.) DC) is very rare and endangered in Switzerland and Central Europe. To provide a basis for its conservation, we present a distribution map with all natural, re-introduced and extinct populations in Switzerland. Only four natural populations of N. pumila still exist in Switzerland: Lac de Lussy and Lac des Joncs (FR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Several recent studies outlined the rapid decay of this species, with almost 20 stations that went extinct in Switzerland over the last century following human-mediated landscape alterations (Kozlowski and Eggenberg 2005). Consistent with these observations, our survey reveals alarmingly low diversity Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Several recent studies outlined the rapid decay of this species, with almost 20 stations that went extinct in Switzerland over the last century following human-mediated landscape alterations (Kozlowski and Eggenberg 2005). Consistent with these observations, our survey reveals alarmingly low diversity Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Together with N. microphylla from North America it belongs to socalled Nuphar-dwarfs since they are much smaller in size and number of floral parts than the most common species N. lutea (Heslop-Harrison 1955;Meusel et al 1965;Padgett 1998Padgett , 2007. Most information on N. pumila in the Alps and surrounding area could be found in the publications of Kozlowski and Eggenberg (2005); Roweck and Reinöhl (1986);and Roweck (1988). Finally, the papers of Heslop-Harrison (1953, 1955 on the genus Nuphar in Great Britain, although published more than half a century ago, remain valuable.…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Roelofs (1986a, 1986b) and Heegaard et al (2001) demonstrated that the phytocoenoses of M. spicatum have a broad ecological amplitude with respect to properties of water, and developed best in waters relatively rich in SO 4 2x . Our results also confirm the distinct character of the habitats of some floating-leaved plant communities, particularly the phytocoenoses of N. pumila, which are found in mostly nutrient-rich (Roweck, 1988;Kozlowski and Eggenberg, 2005) soft waters, poor in Ca 2+ (Kadono, 1982;Roweck, 1988;Kłosowski and Tomaszewicz, 1990;Doll, 1991). The results obtained by some authors confirm our findings for N. lutea (waters rich in Ca 2+ and NO 3 x -Wiegleb, 1978; hard alkaline watersDe Roelofs, 1986a, 1986b;Smits et al, 1988), N. candida (mesotrophic or slightly eutrophic waters Pietsch, 1982; narrow ecological amplitude with respect to Ca 2+ - Van der Velde et al, 1986) and P. amphibium (waters relatively poor in NH 4 + - Wiegleb, 1978).…”
Section: Discussionsupporting
confidence: 80%
“…In some phytosociological works, the relationship of C. demersum to organic substrates was also demonstrated (e.g., Doll, 1991), and in the case of N. alba confirmed by Rejewski (1981). Roweck (1988) and Kozlowski and Eggenberg (2005) indicated that the phytocoenoses of N. pumila were confined to organic substrates. The data obtained by other authors (e.g., Roelofs, 1986a, 1986b;Van Katwijk and Roelofs, 1988) show that the phytocoenoses dominated by species such as P. natans, P. lucens, N. lutea, M. spicatum and M. verticillatum have a wide ecological amplitude with respect to substrate properties.…”
Section: Discussionmentioning
confidence: 99%